1999
DOI: 10.1021/es980402v
|View full text |Cite
|
Sign up to set email alerts
|

Organochlorine Pesticides Removal by Pinus Bark Sorption

Abstract: Pesticides belong to a chemical family that calls our attention because of its hazardous effects in the environment. The organochlorine pesticides were strongly used in the past, but their persistency and bioaccumulation make them an actual problem. Common wastewater treatment methods, like activated carbon sorption, mean expensive investment and operating costs. Pine bark is a wood industry byproduct and has a high affinity with hydrophobic compounds because of its organic composition. The aim of this work is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 14 publications
0
43
1
1
Order By: Relevance
“…However, most of these modified cellulose substrates dealt with the trapping of metallic ions. Few study reported the use of similar system to remove organic pollutants, like pesticide, dissolved organic compound and organic dyes (Bras et al 1999;Ho et al 2005). These recent investigations pointed out that they presented a major drawback concerning the relatively low pollutant-uptake level compared with conventional adsorbents such as activated carbon or zeolite (Perrich 1981;Radovic et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…However, most of these modified cellulose substrates dealt with the trapping of metallic ions. Few study reported the use of similar system to remove organic pollutants, like pesticide, dissolved organic compound and organic dyes (Bras et al 1999;Ho et al 2005). These recent investigations pointed out that they presented a major drawback concerning the relatively low pollutant-uptake level compared with conventional adsorbents such as activated carbon or zeolite (Perrich 1981;Radovic et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…17,20 Removal of cadmium and mercury ions from aqueous solution by sorption on treated Pinus pinaster bark: kinetics and isotherms was studied by Vazquez et al 21 Regarding to the sorption of organic pollutants by pine bark reported interesting results for organochlorine pesticides. 22 Adsorption of phenol on formaldehyde-pretreated Pinus pinaster bark: equilibrium and kinetics was studied by Vazquez et al 23 Acacia leucocephala bark, agricultural and easily available waste, could be an alternative for more costly wastewater treatment processes. Acacia leucocephala's native range through South and Southeast Asia is noncontiguous.…”
Section: Introductionmentioning
confidence: 99%
“…Studies of pollutants removal efficiency using materials as bagasse fly ash, [9,10] diatomaceous earth, [11] chitosan, [12] pinus bark, [13] cork residues [14] and wood chips, [17] have recently shown the consistency and economic advantages of such alternatives. In the western Mediterranean region, and especially in the south of Portugal, cultivation of cork oak is an important economic activity.…”
Section: Introductionmentioning
confidence: 99%